Regional Power Dynamics and Security Approaches: A Comparative Study of SADC and ECOWAS - Akindoyin, Dare Isaac; Obafemi, Akintomiwa Olaniyi (African Journal of Stability and Development (AJSD), 2024)
This study examines regional power dynamics and security approaches within two prominent African regional organisations: ECOWAS– Economic Community of West African States and the SADC– Southern African Development Community. Since Africa remains insecure due to internal conflicts, and terrorism, regional organisations have a vital role in stability. ECOWAS and SADC are particularly marked by their specific security mechanisms; however, they are located in different political, social and economic environments and thus perform differently in terms of management and resolution of conflict. Using the theoretical framework of power theory and the adoption of case study research design and content analysis, the research critically explores regional power dynamics and security approaches within SADC and ECOWAS. The findings reveal that while ECOWAS’s interventionist policies enable swift action, they sometimes face issues of sustainability and regional buy-in. In contrast, SADC’s consensus-driven approach promotes stability but can lead to prolonged conflict resolution processes. This study contributes to the broader discourse on regional security in Africa, highlighting the need for adaptable strategies that address both immediate threats and long-term stability in diverse geopolitical environments. The study concludes that while both SADC and ECOWAS employ different strategies in Western and Southern Africa, yet the approaches are similar in many ways. Consequently, the two organisations though having the common strategic object of creating stability at regional level have significantly different operating models defined by their respective historical, political and socio-economic circumstances. These differences define their security actions, the coordination of the states which are members of the union, and their performance in the handling of conflicts.